Antiapoptotic and antioxidant effects of resistance training with berberine consumption on diazinon induced cardiotoxicity in rats - Reza Niazi; Maghsoud Peeri; Mohammad Ali Azarbayjani (Institue of Medicinal Plants, ACECR, 2020)
Background: Increasing use of pesticides is one of the health hazards. Physical activity and medicinal plants appear to be a strategy to mitigate the adverse effects of these substances. Objective: The purpose of this study was to investigate the effect of resistance training and berberine chloride on apoptosis and oxidative stress markers in the heart tissue of diazinon-infected rats. Methods: In this study, 80 rats were randomly assigned into 8 groups of 10 animals in each group, including: 1) healthy control, 2) sham, 3) diazinon, 4) diazinon + resistance training, 5) diazinon + berberine (2.5 mg/kg) 6) diazinon + berberine (15 mg/kg), 7) diazinon + resistance training and berberine (2.5 mg/kg), and 8) diazinon + resistance training and berberine (15 mg/kg). During 4 weeks, each groups received a certain amount of diazinon poison, berberine chloride and performed three sessions per week of resistance training. Results: In the heart tissue of diazinon-poisoned rats, resistance training had a significant (P ≤ 0.05) effect on the increased concentrations of MDA, caspase-3, 8-OHDG and GSH; 15 mg/kg of berberine consumption had a significant effect on decreased concentrations of ROS, MDA, 8-OHDG, caspase-3 and increased (P ≤ 0.05) concentrations of GSH; 2.5 mg/kg of berberine consumption had a significant (P ≤ 0.05) effect on reduced 8-OHDG. Also, 15 mg/kg of berberine consumption compared to 2.5 mg/kg of berberine consumption had a greater effect on reduced 8-OHDG. Conclusion: It seems that berberine consumption along with resistance training has interactive protective effects against oxidative stress and cell death in the heart tissue of diazinon-poisoned rats.